2014
DOI: 10.3892/ol.2014.1990
|View full text |Cite
|
Sign up to set email alerts
|

Repopulation of tumor cells during fractionated radiotherapy and detection methods (Review)

Abstract: Repopulation of tumor cells during radiotherapy is believed to be a significant cause for treatment failure. The phenomenon of tumor repopulation during fractionated radiotherapy was found from clinical observations that identified that the local control rate decreased with a prolonged treatment time. A series of animal experiments with varied overall treatment time and fractionated doses were performed to demonstrate tumor cell repopulation during radiotherapy in various mouse xenograft models. However, conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 58 publications
2
27
0
Order By: Relevance
“…Histological analysis showed an increase in necrotic foci and a reduced number of proliferating (Ki‐67 positive) cells in H226 tumors treated with 3.70 MBq of 90 Y‐labeled NZ‐12. These histological alterations are frequently observed in tissues damaged by radiation . Our findings suggest that 90 Y‐labeled NZ‐12 has the potential to treat malignant mesothelioma patients.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Histological analysis showed an increase in necrotic foci and a reduced number of proliferating (Ki‐67 positive) cells in H226 tumors treated with 3.70 MBq of 90 Y‐labeled NZ‐12. These histological alterations are frequently observed in tissues damaged by radiation . Our findings suggest that 90 Y‐labeled NZ‐12 has the potential to treat malignant mesothelioma patients.…”
Section: Discussionmentioning
confidence: 58%
“…By replacing 111 In with a therapeutic radionuclide 90 Y, 3.70 MBq of 90 Y-labeled NZ-12 showed a stronger tumor growth suppression effect and prolonged survival frequently observed in tissues damaged by radiation. 40,41 Our findings suggest that 90 Y-labeled NZ-12 has the potential to treat malignant mesothelioma patients.…”
Section: Immunofluorescence Staining Analysis Of Podoplanin Expressionmentioning
confidence: 72%
“…In subsequent years, research results confirmed the presence of cells that expressed stem cell markers in other cancers [ 30 ], including brain, breast, prostate and lung tumors [ 31 , 32 , 33 , 34 , 35 ]. Cancer stem cells are relatively resistant to chemo- and radio-therapy [ 36 , 37 , 38 ], and possibly for this reason, the prognosis is poor for patients whose cancer expresses stem cell markers. Complete healing of the neoplastic process may be related to the elimination of all stem cells [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer stem cells are relatively resistant to chemo- and radio-therapy [ 36 , 37 , 38 ], and possibly for this reason, the prognosis is poor for patients whose cancer expresses stem cell markers. Complete healing of the neoplastic process may be related to the elimination of all stem cells [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sub-curative doses of radiation can result in the onset of accelerated-repopulation, and makes subsequent re-initiation of therapy difficult. [ 10 11 ] However, this is a neglected issue, and the adverse impact of non-compliance upon the cure-rates is often not provided due emphasis.…”
Section: Discussionmentioning
confidence: 99%